34. RETROSPECTIVE PGT-A ANALYSIS FOR MULTIPLE DISPLACEMENT AMPLIFICATION PRODUCTS OF EMBRYOS CORRESPONDING TO 104 LIVE BIRTHS BY NEXT-GENERATION SEQUENCING (NGS). (August 2019) - Shen, X.; Chen, D.; Fu, Y.; Ding, C.; Xu, Y.; Zhong, Y.; Xu, Y.; Zhou, C.
Abstract : Introduction: Preimplantation genetic testing for aneuploidy(PGT-A) has been widely used, but its clinical application value is still inconclusive. The previous PGS 1.0 technology has been proven to have a negative impact on IVF outcomes. PGS 2.0, blastocyst biopsy combined with high-throughput detection technology, has gradually became the mainstream detection method of PGT-A.Many problems still exist in this technology: 1. Biases caused by whole genome amplification (WGA) or high-throughput detection techniques; 2.Embryo mosaicism.Mosaic embryos were used to be considered unsuitable for transfer. However recently healthy live births after transferring mosaic embryo have been widely reported. And many studies also found that some embryos diagnosed as abnormal by PGT-A were turned out to be normal after retested with their inner cell mass. It is therefore suggested that there may be false positive results in PGT-A technology, resulting in the waste of many valuable embryos with normal developmental potential. The interpretation of PGT-A results in clinical practice remains deficient.Since 2015, our center has adopted multiple displacement amplification (MDA) as the first step of all PGT cycles, so we have established a library of MDA products. Material & methods: We investigated PGT cycles conducted for monogenic diseases (PGT-M) between January 2015 and December 2017 in our center. Eligible cycles were in which the blastocyst biopsy and single blastocyst transfer were adopted and healthy live birth was obtained. Exclusion criteria: Cycles in which PGT-A had been performed and the embryo was selected based on PGT-A results. MDA used Repli-g MiDi kit(Qiagen, Germany) or Repli-g Single cell kit(Qiagen, Germany) .All MDA products were conducted PGT-A using next generation sequencing (NGS) by Illumina NextSeq® 550 platform. We sequenced the amplified genome of each sample at approximately 0.01x genome depth and the resolution of chromosomal abnormality detection was 4Mb. Results: A total of 103 MDA products were tested, of which 11 failed to amplify. Among the 92 successful amplified products, 47 used the Midi-MDA kit while 46 used the Single cell-MDA kit. The average standard deviation(SD) value of NGS data was 3.58 (2.09-9.25).The PGT-A results showed that: 35.9%(33/92) embryos were euploidy; one was trisomy 22; 30.4%(28/92) embryos were mosaic whole chromosomal aneuploidy (the proportion of mosaicism range from 20% to 41%);6.5% (6/92) embryos were segmental chromosomal aneuploidy(chromosomal fragment length of duplication or deletion range from 4.06 Mb to 191.01 Mb), and 8.7% (8/92) embryos were mosaic segmental aneuploidy; 17.4% (16/92) embryos had segmental aneuploidy combined with mosaic aneuploidy. Overall, mosaic chromosomal aneuploidy was detected in 56.5% (52/92) blastocysts which could produce healthy babies.Prenatal diagnosis or karyotype detection of the newborns were performed in 31 cases and all the results were euploidy. Conclusions: Our study demonstrated that PGT-A would lead to the waste of viable embryos, so it should be questioned whether all mosaic embryos and segmental aneuploidy embryos should be abandoned. How to correctly interpret the results of PGT-A is an urgent problem.